The synergistic effect of organically modified sepiolite in intumescent flame retardant polypropylene. (March 2016) - Pappalardo, Salvatore; Russo, Pietro; Acierno, Domenico; Rabe, Sebastian; Schartel, Bernhard
Graphical abstract: Highlights: Polypropylene systems involving sepiolite clays and a flame retardant are investigated. Clays do not affect the thermo-oxidative stability of polypropylene/flame retardant systems. Systems containing 0.5 wt% of organomodified sepiolite clay show synergistic effects. TEM micrographs show a satisfying filler dispersion especially in ternary systems. Thermal results are partially supported by dynamic rheological evaluations. Abstract: The pyrolysis, flammability and fire behavior of polypropylene (PP) containing an intumescent flame retardant and sepiolite nanoparticles were investigated by performing thermogravimetry, oxygen index (LOI), UL-94, and cone calorimeter tests. The combination of 0.5 wt% of premodified sepiolite (OSEP) with 12 wt% of a commercial intumescent flame retardant showed a clear synergy in LOI, UL-94 ranking and peak heat release rate. The ternary formulation achieved a V-0 classification and, consequently, allowed a reduction in the amount of flame retardant necessary to achieve this result. Whereas OSEP and pristine sepiolite nanoparticles (SEP) affect the performance in PP nanocomposites quite similarly, OSEP outperformed SEP in the combination with intumescent flame retardant. The cone calorimeter results and dynamic rheological measurements confirmed the synergistic effect between the nanofiller and the flame retardant resulting from the improved properties of the residual protective layer.